Eugenol specialty chemical production in transgenic poplar (Populus tremula × P. alba) field trials. Issue 8 (7th March 2017) - Lu, Da; Yuan, Xianghe; Kim, Sung‐Jin; Marques, Joaquim V.; Chakravarthy, P. Pawan; Moinuddin, Syed G. A.; Luchterhand, Randi; Herman, Barri; Davin, Laurence B.; Lewis, Norman G.
Summary: A foundational study assessed effects of biochemical pathway introduction into poplar to produce eugenol, chavicol, p ‐anol, isoeugenol and their sequestered storage products, from potentially available substrates, coniferyl and p ‐coumaryl alcohols. At the onset, it was unknown whether significant carbon flux to monolignols vs. other phenylpropanoid (acetate) pathway metabolites would be kinetically favoured. Various transgenic poplar lines generated eugenol and chavicol glucosides in ca . 0.45% (~0.35 and ~0.1%, respectively) of dry weight foliage tissue in field trials, as well as their corresponding aglycones in trace amounts. There were only traces of any of these metabolites in branch tissues, even after ~4‐year field trials. Levels of bioproduct accumulation in foliage plateaued, even at the lowest introduced gene expression levels, suggesting limited monolignol substrate availability. Nevertheless, this level still allows foliage collection for platform chemical production, with the remaining (stem) biomass available for wood, pulp/paper and bioenergy product purposes. Several transformed lines displayed unexpected precocious flowering after 4‐year field trial growth. This necessitated terminating (felling) these particular plants, as USDA APHIS prohibits the possibility of their interacting (cross‐pollination, etc.) with wild‐type (native plant) lines. In future, additional biotechnological approaches can be employed (e.g. gene editing) to produce sterile plant lines, to avoid such complications. While increased gene expression did not increase target bioproduct accumulation, the exciting possibility now exists of significantly increasing their amounts (e.g. 10‐ to 40‐fold plus) in foliage and stems via systematic deployment of numerous 'omics', systems biology, synthetic biology and metabolic flux modelling approaches.